Risk Factors for Death from Visceral Leishmaniasis in an Urban Area of Brazil. - Angelita F Druzian; Albert S de Souza; Diogo N de Campos; Julio Croda; Minoru G Higa; Maria Elizabeth C Dorval; Mauricio A Pompilio; Polliana A de Oliveira; Anamaria M M Paniago (Public Library of Science (PLoS), 2015)
BACKGROUND:Over the last three decades, the epidemiological profile of visceral leishmaniasis (VL) has changed with epidemics occurring in large urban centers of Brazil, an increase in HIV/AIDS co-infection, and a significant increase in mortality. The objective of this study was to identify the risk factors associated with death among adult patients with VL from an urban endemic area of Brazil. METHODOLOGY:A prospective cohort study included 134 adult patients with VL admitted to the University Hospital of the Federal University of Mato Grosso do Sul between August 2011 and August 2013. PRINCIPAL FINDINGS:Patients ranged from 18 to 93 years old, with a mean age of 43.6 (±15.7%). Of these patients, 36.6% were co-infected with HIV/AIDS, and the mortality rate was 21.6%. In a multivariate analysis, the risk factors associated with death were secondary bacterial infection (42.86, 5.05-363.85), relapse (12.17, 2.06-71.99), edema (7.74, 1.33-45.05) and HIV/AIDS co-infection (7.33, 1.22-43.98). CONCLUSIONS/SIGNIFICANCE:VL has a high mortality rate in adults from endemic urban areas, especially when coinciding with high rates of HIV/AIDS co-infection.